Using of Communication Technology and the Future Role of the State of Qatar in the Distance Education - Mohamed, Mervat Rashad Ibrahim (American Journal of Management, 2021)
The study aimed to identify the developmental and future role that Qatar plays in the field of distance education and communication technology, highlighting the scientific and research capabilities that the State of Qatar provides to the public, and ways to develop the scientific and educational aspects for the advancement of the state and study the problems that constitute an obstacle to the maximum benefit from communication and education technology From distance and to identify the extent to which educational and research institutions in the State of Qatar benefit from communication technology. The study relied on the survey method. The study used an electronic questionnaire form and relied on a sample consisting of (400) single people. The study concluded that 59% of the study sample are highly satisfied with the efforts of the State of Qatar in The field of distance education, while (27%) of them were satisfied with a medium degree, while (14%) of them came with a low degree, and it was found that (36%) of the study sample use educational content provided through modern communication technology, and a percentage (20%) of them are sometimes What are they looking for on those contents